Efficacy and Safety of Direct-Acting Oral Anticoagulants Use in Acute Portal Vein Thrombosis Unrelated to Cirrhosis - Nery, F (2017)
In acute portal vein thrombosis (APVT) unrelated to cirrhosis, anticoagulant therapy is classically started with low molecular weight heparin or vitamin K antagonists. New direct-acting oral anticoagulants (DOACs) are used in the treatment of venous thrombosis outside the splanchnic vascular bed, but not in the latter. We report a young female with APVT occurring in a non-cirrhotic liver linked to heterozygosity of factor V-Leiden and prothrombin G20210A gene mutations. Rivaroxaban was started, with total recanalization of the left and partial recanalization of the right portal vein branches, without complications. New DOACs do not need daily subcutaneous injections nor routinely blood coagulation control tests, making its use attractive, eventually increasing patient’s compliance. If proved to be safe and effective in the future studies, its use may be extended to PVT treatment. This case shows that rivaroxaban was safe, not only prevented the extension of thrombosis in the portal tract, but also resolved PVT, at least partially.